Notes about Czerniawski - Kisiel, Marian (Tematy i Konteksty, 2021)
The article constitutes a collection of notes related to the lesser known and rarely commented works by an émigré writer – Adam Czerniawski: his poems translated into English, short texts of literary criticism, short novels and his memoirs. Modern Polish prose is still frequently treated as a ciphertext, of interest only to a limited number of readers who revel in this labyrinth of thoughts. It may seem that at the end of the 20th century – a period so involved in the debate about the traditional understanding of literature – avant-garde variants of prose should be understandable for everyone or, at least, that literary criticism would assign them to the appropriate level in the hierarchy of modern forms. However, the situation turned out to be different. The prose model imposed by Positivism still remains predominant in the habits and tastes of both literary critics and readers, and only recently has this model been questioned. As a result, the short novels by Czerniawski have not yet been sufficiently analysed. Reminiscent of Gombrowicz, these texts can be seen as absolute stories. The feature of absoluteness is visible at all their levels: origin, narration, reading. Everything is possible, yet nothing is accidental or random. However, limiting these narratives to only avant-garde rules would, without a doubt, distort their sense. Czerniawski’s prose also uses the infinite potential of the grotesque, plays with its own language, thus making it into an undoubtedly philosophical Ding an sich. The prose was also written in order to face traditional sanctities such as, for instance, the incorrigible “Polishness” that glorifies old symbols and sees a divine influence in them. Finally, Czerniawski’s prose is based on the “common sense” that can be found in numerous amusing contexts of the surrounding world.